Novel Evaluation Method for Site Effect on Earthquake Ground Motion Based on Modified Horizontal to Vertical Spectral Ratio - Li, Xiaojun; Li, Na; Rong, Mianshui; Dong, Qing (Frontiers in Earth Science, 2022)
The effect of local site condition on earthquake ground motion is a very important factor to be considered in engineering seismic fortification. Many methods, such as numerical simulation methods based on site analysis models, statistical empirical relation methods based the earthquake ground motion observation and numerical simulation data, etc., are used to consider the site effects in the actual engineering seismic fortification and earthquake disaster assessment. The statistical analysis to obtain characteristic parameters of site condition effect based on strong motion and microtremor records has become a more economical and practical method to determine the design ground motion of engineering sites, especially for a large survey area or an engineering site that are difficult to carry out site survey. In this study, a novel evaluation method for site effect on earthquake ground motion is proposed. The new method is derived from the horizontal to vertical spectral ratio (HVSR) method, but the original HVSR is replaced by a modified HVSR considering the effect of soil layer on vertical ground motion. In order to build the model and corresponding parameters of the modified HVSR, first, the differences between the ground surface to bedrock spectral ratio (SBSR) and the HVSR for the local sites of ground motion observation stations were analyzed by using the strong ground motion records from the Japanese KiK-net network, and the statistical characteristics of the relation between SBSR and HVSR were revealed, and then a quantitative relationship between SBSR/HVSR and HVSR was established. The proposed evaluation method for site effect has the advantage that the original HVSR method only requires ground motion records on the ground surface of site, and further considers the influence of the vertical seismic effect on the accuracy of the HVSR method. The proposed method can more reasonably characterize the influence of site conditions on ground motion.